THE INDIVIDUAL AND THE PROPERTY IN VIRTUAL WORLDS - Koos, Stefan (Faculty of Law, Parahyangan Catholic University, 2022)
Virtual reality and augmented reality have the potential to change the economy and society as much as the internet once did. In AR, virtual objects mix with real environments and objects. In virtual reality environments, people will move around using avatars and using virtual objects and individualise their virtual spaces with virtual artworks. However, the integration of humans into virtual and semi-virtual environments also leads to an intensification of problems connected with the relationship of the individual to technology and powerful platforms. The person integrated into virtual worlds will be under far closer observation and influence by platform operators than today's internet user. This must have consequences for the legal protection of personality. In addition, questions arise about the extension of personality rights to the virtual existence of the individual and to the question of the legal protection of objects used by the individual in his or her virtual environment. The article discusses some aspects from the perspective of the German law.